Molecular Characteristics and Pathogenicity of Porcine Reproductive and Respiratory Syndrome Virus (PRRSV) 1 in Taiwan during 2019–2020 - Fu-Chun Hsueh; Kun-Lin Kuo; Feng-Yang Hsu; Sheng-Yuan Wang; Hsien-Jen Chiu; Meng-Tien Wu; Chuen-Fu Lin; Yu-Han Huang; Ming-Tang Chiou; Chao-Nan Lin (Life, 2023)
Two variants of porcine reproductive and respiratory syndrome virus (PRRSV), PRRSV 1 and PRRSV 2, have caused abortion in pregnant sows and respiratory distress in nursery pigs worldwide. PRRSV 2 has been thoroughly researched in Taiwan since 1993; however, the first case of PRRSV 1 was not reported until late 2018. To decipher the genetic characteristics of PRRSV 1 in Taiwan, open reading frame 5 (ORF5) genes of PRRSV 1 strains collected from 11 individual pig farms in 2019–2020 were successfully sequenced. All Taiwanese ORF5 sequences were closely related to Spanish-like PRRSV strains, which are considered to share a common evolutionary origin with the strain used for the PRRSV 1 vaccine. Analyses of amino acid (aa) and non-synonymous substitutions showed that genetic variations resulted in numerously specific codon mutations scattered across the neutralizing epitopes within the ORF5 gene. The PRRSV 1 challenge experiment disclosed the pathogenetic capability of the NPUST2789 isolate in nursery pigs. These findings provide comprehensive knowledge of the molecular diversity of the PRRSV 1 variant in local Taiwanese fields and facilitate the development of suitable immunization programs against this disease.